Effect of Hedging, Financial Lease, Sales Growth, and Earning Management on Tax Aggressiveness - Nurwita Mulyaningsih; Ayu Noorida Soerono; Mukhtar Mukhtar (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to examine the effect of hedging, financial leases, sales growth, and earnings management on tax aggressiveness. The research sample consisted of 37 manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The data used in this study is secondary data and the sample selection uses a purposive sampling method. The hypothesis was tested by means of multiple regression analysis which was processed using SPSS version 22. Based on the results of the analysis, it showed that sales growth had a negative effect on tax aggressiveness. Financial lease has positive effect on tax aggressiveness. While hedging and earnings management have not been able to prove the influence of tax aggressiveness.